Rectangular hybrid element applied to shear wall analysis - Medina, Enrique C.
This thesis is about a new type of rectangular element applied in the static analysis of shear wall-frame structure. This element is a hybrid element but with rotational degree of freedom added at its corners. This degree of freedom simplifies the discretization of the structure into finite element meshes and the computer program when either or both beams and columns connected to shear walls are encountered. All the matrices of this element were derived in detail. Early type of elements used for the same purpose were also discussed and a computer program was written that can analyze structures the uses either or both line element and this element for its representation.